Diskursus Mengenai Keadilan Sosial: Kajian Teori Keadilan dalam Liberalisme Locke, Persamaan Marx, dan 'Justice as Fairness' Rawls - Alwino, Alfensius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2016)
Through the history of philosophy, the theme of justice has become a very important topic. Thinkers of the theories such as utilitarianism, intuitionism, eudaimonism, perfectionism, liberalism, communitarianism, and socialism have discussed the theme. As French philosopher Alain Badiou has pointed out, the central of political studies from the time of Plato to the present day is justice. The question is what is justice? For John Rawls, justice is the supreme virtue of human. In A Theory of Justice, Rawls asserts that justice is the first priority in social institutions, as is truth in the system of thought. A theory, however elegant and economical, must be rejected or revised if it is not true, so the laws and institutions, however efficient and neat, must be reformed or removed if it is unfair. Rawls criticizes the theory of justice in Lockean liberalism and Marxian socialism. Both theories of justice are very strong colouring the landscape of debate on the roots of thinking about justice. For Rawls, liberalism that accentuates basic freedoms can create inequality between people who have better abilities with less fortunate people. Similarly, socialism which accentuates equality ignores basic freedoms. The two theories of justice are considered ideological in the sense that there are hidden interests behind the jargons of freedom and equality. Rawls then develops an abstract theory of justice, in which the participants depart from a veil of ignorance, so that they are free of any interest and ambition. Here they might build a cooperative contract in a society governed by the principles of justice.